HUBUNGAN POWER OTOT TUNGKAI DENGAN KEMAMPUAN SHOOTING UNDER RING SISWA PUTRA YANG MENGIKUTI EKSTRAKURIKULER BOLA BASKET SMP NEGERI 13 PEKANBARU - Khairunnisa Rubi Sundra Weti; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The background of male extracurricular basket students at SMP Negeri 13 Pekanbaru, where children are still not able to optimize the jump and throwing power in shooting under the ring, this is seen when doing daily play practice before competing with junior high school students Dharma Yudha many players do not meet the desired Shot Under Under Ring result given the leg muscle strength. The purpose of this Research was to Research the correlation of leg muscle strength to the ability to Shoot Under the Ring of male students who use extracurricular baskets at SMPN 13 Pekanbaru. The objects of this research were 12 students who took basketball extracurricular at SMP Negeri 13 Pekanbaru, and were conducted in April-August 2019. The instrument was taken by using the vertical jump test for leg muscle power variable (X), the ability to take pictures under the ball ring baske (Y). From the results of the Research, the normality test data obtained by using the lilifors test with a significant level α = 0.05, shows the variable (X) Lo = 0.23≤ Ltable 0.249, and the variable (Y) Lo = 0.14≤ Ltable 0.249, the correlation between variable when testing the product moment shows r count = 0.989> r table = 0.602, so it is a variable correlation between leg muscle strength and the ability to shoot under the basketball hoop.Key Words: Leg Muscle Power, Ability To Shoot Under The Basketball.